Case report: Epstein–Barr virus and constrictive pericarditis—An unusual combination - Panebianco, Mario; Limonjiani, Eduard; Formigari, Roberto; Bordonaro, Veronica; Secinaro, Aurelio; Cetrano, Enrico; Carotti, Adriano; Galletti, Lorenzo; Albanese, Sonia (Frontiers in Pediatrics, 2023)
Constrictive pericarditis is a chronic inflammatory process that can lead to heart failure if not diagnosed and treated correctly. Epstein-Barr virus (EBV) related pericarditis is a very rare condition; however, it should still be considered for a differential diagnosis. We report the case of an 18-year-old male, surgically treated for constrictive pericarditis, in which in situ hybridization to Epstein-Barr virus-encoded RNA (EBER) probe of the excised pericardium led to the subsequent etiological diagnosis of chronic pericarditis caused by EBV